Social Media Adoption in the Marketing Strategy of Radiant Buket SME: A UTAUT Model Approach - Bindas, Asniati; Pawirosumarto, Suharno; Lusiana, Lusiana; Sari, Silvia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The advancement of digital technology has encouraged SMEs to adopt social media as part of their marketing strategies to enhance customer engagement and expand market reach. This study aims to analyze the factors influencing social media adoption by Radiant Buket SME using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The key variables examined include performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC), which are hypothesized to affect behavioral intention (BI) and actual use behavior (UB) of social media. Radiant Buket’s marketing strategy involves the use of platforms such as Instagram and TikTok for product promotion, direct customer interaction, and the dissemination of information and testimonials through visual content. The findings show that PE and SI have a positive influence on BI, indicating that perceived usefulness and social encouragement drive the intention to adopt social media. Although EE has a negative effect, it still significantly influences BI, suggesting that users are willing to adopt social media despite perceiving it as requiring more effort. Additionally, FC positively affects UB, and BI significantly impacts UB, indicating that strong intention indeed leads to actual usage behavior. These findings offer practical insights for Radiant Buket in strengthening its digital marketing strategy, particularly through customer-oriented promotional content, enhanced two-way interaction on social media, and the optimization of support resources such as staff training and digital infrastructure. Theoretically, this study enriches the literature on technology adoption in the context of Indonesian SMEs, particularly in applying the UTAUT model within digital marketing. It also highlights the importance of a data-driven approach in developing sustainable and effective social media marketing strategies.